Acute Appendicitis: Hispanics and the Hamburger Sign - C, Garcia Gubern; Rolón L, Colon; Mercado I, Ruiz; Garcia C, Oliveras; Acosta D, Caban; Pagán J, Muñoz; I, Iriarte; Ávila G, Bolaños; Rivera J, Peguero; Gaetan F, Sánchez; Castro J, Oneill; Paola N, Cordero Colón; et al. (Archives of Surgery and Clinical Research, 2019)
Objective: To describe the presenting clinical findings of patients with acute appendicitis and compare them with those described in the medical literature. To corroborate a common medical myth among Hispanic physicians regarding the presentation of acute appendicitis. Methods: This was a retrospective multicenter chart review of patients diagnosed post-operatively with appendicitis after presenting to five different Emergency Departments in Southern Puerto Rico (PR). Results: A total of 1,540 patients with pathologically confirmed cases of appendicitis were enrolled in our study. Of the study population, 45% were female, and 55% were male, and 43% were over 21 years old. Reported symptoms in our study showed that 98% of the patients had abdominal pain, 47% had nausea, and only 17.6% presented with anorexia. Conclusion: It was our main objective to compare the presenting signs and symptoms of patients with acute appendicitis in our Hispanic population in southern PR with those found in primary medical textbooks and literature. We gathered information regarding signs and symptoms, as well as laboratory and radiographic data of patients with positive pathologic exams for appendicitis. Of the 1,540 patients with confirmed appendicitis, only 17.6% presented with anorexia. Our findings demonstrate that the rate of anorexia in the studied population is significantly lower when compared to current literature. The absence of anorexia, once considered a hallmark of appendicitis, must not lead the physician to rule out this diagnosis in the Hispanic population.